2016
DOI: 10.1590/s0102-865020160040000005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low level laser therapy on Staphylococcus aureus infected third-degree burns in diabetic rats

Abstract: The low-level laser improved the healing of S. aureus third-degree burn infections in diabetic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
1
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
(36 reference statements)
2
13
1
6
Order By: Relevance
“…24,16,39,22,23 Ranjbar and Takhtfooladi have reported the positive effects of LLLT(685 nm, 5 sequential sessions, 40 J/cm 2 ) on wound contraction and wound strength in third-degree burn wounds that were infected with S. aureus in TIDM rats. 24 They reported average bacterial count in the experimental group was significantly lower than that in the control group on day 21. 24 Asghari et al reported positive influences of LLLT [or photobiomodulation (PBM), 890 nm, 80 Hz, 300 s duration, 0.324 J/cm 2 energy density] on the microbial flora and tensiometerical parameters of wounds in a nongenetic model of TIIDM compared to the placebo and metformin groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24,16,39,22,23 Ranjbar and Takhtfooladi have reported the positive effects of LLLT(685 nm, 5 sequential sessions, 40 J/cm 2 ) on wound contraction and wound strength in third-degree burn wounds that were infected with S. aureus in TIDM rats. 24 They reported average bacterial count in the experimental group was significantly lower than that in the control group on day 21. 24 Asghari et al reported positive influences of LLLT [or photobiomodulation (PBM), 890 nm, 80 Hz, 300 s duration, 0.324 J/cm 2 energy density] on the microbial flora and tensiometerical parameters of wounds in a nongenetic model of TIIDM compared to the placebo and metformin groups.…”
Section: Discussionmentioning
confidence: 99%
“…PW LLLT accelerated the wound‐healing process in streptozotocin (STZ)‐induced TIDM, as measured by tensiometerical parameters and histological characteristics, and significantly reduced the colony‐forming units (CFUs) of bacteria in non‐genetic rat models of Types 1 and 2 . In 2016, Ranjbar and Takhtfooladi reported positive effects of CWLLLT (685 nm, 3 J/cm 2 , 5 days) on infected burns with MRSA in TIDM animals …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel approaches to treat MRSA contamination and counter the growing complication of MRSA are mandatory 34. Specifically, our experiment aimed to focus on the bactericidal effects of PBM47 and ADS34 because both have been individually reported to have bactericidal effects in animal models. To date, there is no probe that has examined the effects of PBM on immunomodulation of ADS.…”
Section: Discussionmentioning
confidence: 99%
“…Different course of antibiotic resistance, especially in methicillin resistant Staphylococcus aureus (MRSA) demand a new approach to management of innovative treatments [3]. To manage medical treatment of infected wounds, lots of agents and protocols have been proposed in the literature [4,5].…”
mentioning
confidence: 99%